ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INFLASI DI INDONESIA 2007-2012 - Kurniawan Saputra; Nugroho SBM (Diponegoro Journal of Economics, 2014)
ABSTRACTThe decision maker should now what factors which influence a variable so that can formulate the appropriate policy to control it. This research is willing to analyze the impact of money supply, exchange rate Rp/US$, interest rate, and rice prices to the inflation in Indonesia.This research uses ARCH/GARCH model selection by comparing one model to another. The best model was chosen by considering some criteria, like: R2 value, adjusted R2 value, AIC & SIC value, significance look up, and detection the violations of classical assumption. After going through selection process, and then it was decided to choose EGARCH-M 2.2 as the best model.The regression output using EGARCH-M 2.2 (by including log variance to the mean equation) and including rice prices into variance regressor, the result showed that money supply, exchange rate, rice prices individually has positive and significant relationship to the inflation in Indonesia. Otherwise, interest rate has positive but not significant to the inflation in Indonesia.